Rancang bangun miniatur kereta elektromagnetik sebagai media untuk menjelaskan konsep listrik magnet berbasis laboratorium mini - Winarti, Septi; Sohibun; Mardiansyah, Dedi (Jurnal Pendidik Indonesia, 2020)
This study aims to design an electromagnetic train learning media based on a mini-laboratory and test the feasibility of this media in explaining the concept of magnetic electricity in the subtopic of electromagnetic induction. This research is an engineering study. The design of this device consists of three main components: a neodymium magnet 12x5 mm, a non-insulated enamel copper wire 1 mm, and a 1.2 V eneloop battery. The device's validity was assessed in terms of content, media, and device feasibility, which was evaluated by two lecturers, three teachers, and two colleagues using a questionnaire distribution technique. The data analysis technique used in this research is the descriptive analysis technique. Based on the questionnaire results from the experts, an average score of 88.46% was obtained for all assessment aspects, indicating a "very good" rating. Thus, the electromagnetic train media is suitable as a physics learning media to explain the concept of magnetic electricity based on a mini laboratory.